The Influence of Gender Diversity, Firm Life Cycle, and ESG Disclosure on Financial Distress in Energy Companies on the IDX - Lhantiraa, Regininna Malva; Dewi, R Rosyiana (JESI (Jurnal Ekonomi Syariah Indonesia), 2024)
The existence of a business is crucial for a country's economy, making the bankruptcy of such businesses a matter of concern for all stakeholders. Therefore, this study aims to determine the factors that contribute to financial distress in energy companies in Indonesia. The independent variables in this study are gender diversity, firm life cycle, and ESG disclosure. The sample used in this study consists of energy companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The research employs a quantitative method, utilizing descriptive statistical analysis, panel data regression analysis, classical assumption tests, and hypothesis testing for analysis. The analysis tool used is E-Views 12. The results of this study are as follows commissioner gender diversity and director gender diversity do not affect financial distress, while Audit Committee Gender Diversity hurts financial distress. Firm life cycle introduction, firm life cycle growth, and firm life cycle decline do not affect financial distress, while firm life cycle maturity hurts financial distress. ESG disclosure does not affect financial distress. This study aims to provide information and references for stakeholders, academics, and practitioners interested in analyzing financial distress to support decision-making and further research.